2019
DOI: 10.1186/s12879-019-4008-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of tuberculosis and its association with meteorological factors in mainland China

Abstract: Background The incidence of tuberculosis (TB) remains high worldwide. Current strategies will not eradicate TB by 2035; instead, by 2182 is more likely. Therefore, it is urgent that new risk factors be identified. Methods An ecological study was conducted in 340 prefectures in China from 2005 to 2015. The spatial distribution of TB incidence was shown by clustering and hotspot analysis. The relationship between the distribution patterns and six meteorological factors wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 20 publications
4
47
1
Order By: Relevance
“…[40] However, meteorological factors may play an important role. Our findings showed that low RH decreased the risk of TB for temperature which was different from Yingjie Zhang's research [41]. In cold temperature situation, the increased RH may create a suitable environment for the growth and reproduction of tuberculosis.…”
Section: Discussioncontrasting
confidence: 91%
“…[40] However, meteorological factors may play an important role. Our findings showed that low RH decreased the risk of TB for temperature which was different from Yingjie Zhang's research [41]. In cold temperature situation, the increased RH may create a suitable environment for the growth and reproduction of tuberculosis.…”
Section: Discussioncontrasting
confidence: 91%
“…Notifications of child PTB only accounted for 0.6% of all notified PTB cases, with the maximum proportion of child TB cases in Tibet (2.85%) and minimum proportion in Jiangsu (0.28%) (online supplementary table 1). Although the incidence of both populations showed a downward trend over the 7 years, the decline in child PTB was more rapid than that in the non-child age PTB group (52.5% vs 21.2%) 9 10. Similar to PTB in the whole population, the spatial distribution of PTB in children showed a high incidence in the west and a low incidence in the east of China (online supplementary figure 1 and figure 3).…”
Section: Resultsmentioning
confidence: 90%
“…Similar to PTB in the whole population, the spatial distribution of PTB in children showed a high incidence in the west and a low incidence in the east of China (online supplementary figure 1 and figure 3). 9 10 However, the peak period of notified child PTB, when mainly occurring from March to July and covering spring and early summer, appeared later and longer than that of all age PTB 9. Regarding laboratory tests, the positive rates of X-ray abnormality and sputum smear and bacteriology in the children with PTB were lower than those in the ≥15 years age group population (all p values <0.001).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The possible link between PTB and meteorological factors may be attributed to the between PTB and atmospheric pressure may be related to wind speed, but further exploration is needed [27]. Third, high relative humidity and abundant precipitation can provide an appropriate living environment for M.tb [27,28]. Continuous exposure to dry air may decrease the production of protective mucus on the respiratory tract surface, thereby weakening its resistance to the pathogen [29].…”
Section: Discussionmentioning
confidence: 99%